Deleterious influence of water logging on potato in warm climates - Ekanayake, I.J. (International Society for Horticultural Science, 1994)
Water logging is a potential abiotic stress problem in the warm tropical potato growing areas, particularly in the lowland rice-based cropping systems. A field experiment was conducted in San Ramon, Peru during the rainy season to evaluate the effects of water logging on 12 clones (8 lowland tropical adapted clones and 4 highland adapted clones). A single week-long flooding period during the tuberization stage was sufficient to significantly reduce the tuber productivity of most clones. The flood treatment however had a yield enhancement effect in a few late clones. Flooding significantly reduced the number of tubers and the visual acceptance quality of the tubers. Effect of flooding on the dry-matter content, weight of rotten tubers, and harvest index varied among clones. Physiological effects of flooding were further evaluated using flood tanks and in-vitro multiplied plantlets transplanted in “jiffy” pots and tested in flooded trays. Plant survival was severely reduced by the flooding stress and a difference in the leaf water potential was noted. Clonal differences in response to the stress indicated a high potential for the selection of tolerant types.